Role of videocapillaroscopy in early detection of transition from primary to secondary Raynaud's fenomenon in systemic sclerosis - B. Seriolo; S. Paolino; M. Parodi; C. Pizzorni; M. Grollero; A. Sulli; M.E. Secchi; M. Cutolo (PAGEPress Publications, 2011)
Patients initially diagnosed as having primary Raynaud's phenomenon (PRP) may shift to secondary (SRP) during the follow-up. Nailfold videocapillaroscopy (NVC) is a tool that allows to distinguish between PRP and SRP through the identification of the "early" scleroderma-pattern of microangiopathy. The aim of this study was to evaluate the transition from PRP to SRP in an Italian cohort of patients during their follow-up. 129 patients with PRP were identified and followed-up for 2721 months. The diagnosis of PRP was achieved as suggested by LeRoy. The NVC diagnosis of scleroderma-pattern was based on the presence of specific "early" capillary abnormalities (i.e. giant capillaries, microhaemorrhages, and/or slight reduction of capillary density). Based on the identification of the "early" scleroderma-pattern by NVC, 14% of patients changed from PRP to SRP during the follow-up. Interestingly, 4.6% of these patients showed at baseline a fully normal NVC pattern (transition from normal to scleroderma NVC pattern in 3427 months), and 10% showed slight and not-specific nailfold capillary abnormalities (i.e. dystrophic capillaries and/or enlarged capillaries) at baseline (transition to scleroderma NVC pattern in 2515 months). Following a careful NVC analysis, we showed the progression from PRP to SRP in 14% of the analyzed patients. We suggest the capillaroscopic analysis twice a year in presence of PRP, in order to early detect the transition to SRP in patients showing at the beginning a normal pattern or not-specific nailfold capillary abnormalities, as assessed by NVC.